Effect of microwave-assisted acid or alkali pretreatment on sugar release from dragon fruit foliage - Mohammad, Saleem Ethaib; Omar, Rozita; Mustapa Kamal, Siti Mazlina; Awang Biak, Dayang Radiah; Syam, Syafiie; Harun, Mohd Yusof (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Agriculture residues are a promising feedstock for value-added products from lignocellulosic waste. However, pretreatment of lignocellulosic materials is essential to facilitate enzymatic hydrolysis and improve sugar yield. The objective of this study is to evaluate the effect of acid or alkali during microwave-assisted pretreatment of dragon fruit foliage (DFF) that would make hydrolysis process more efficient. In the present study, distilled water and three chemicals were examined for their effects on releasing monomeric sugar during microwave treatment. Microwave-assisted pretreatment namely microwave-distilled water (M-H2O) (control); microwave-sulfuric acid (M-H2SO4); microwave-sodium hydroxide (M-NaOH); and microwave-sodium bicarbonate (M-NaHCO3) pretreatment were performed using 5% (w/v) of DFF as substrate at 800 watt microwave power for 5 minutes exposure time. Highest yield of monomeric sugar was found at 15.56 mg/g using M-NaOH pretreatment at 0.1N NaOH. For M-H2SO4 pretreatment, 0.1N H2SO4 produced 8.2 mg/g of monomeric sugar. Application of M-NaHCO3 pretreatment using 0.05N NaHCO3 solution released 6.45 mg/g of monomeric sugar. While, soaking DFF in distilled water and subjecting to microwave irradiation released 6.6 mg/g of monomeric sugar. Treatments with the lowest concentration (0.01 N) of the three chemicals released only small quantities of total monomeric sugars and less than that with distilled water. The changes in the physical structure of DFF prior to and after the microwave-assisted pretreatment are also reported.